Disparities by Race and Ethnicity in Cancer Survivor Stories Available on the Web - Eddens, Katherine S; Kreuter, Matthew W; Morgan, Jennifer C; Beatty, Kate E; Jasim, Sina A; Garibay, Lori; Tao, Donghua; Buskirk, Trent D; Jupka, Keri A (JMIR Publications, 2009)
Background The rapid growth of eHealth could have the unintended effect of deepening health disparities between population subgroups. Most concerns to date have focused on population differences in access to technology, but differences may also exist in the appropriateness of online health content for diverse populations. Objective This paper reports findings from the first descriptive study of online cancer survivor stories by race and ethnicity of the survivor. Methods Using the five highest-rated Internet search engines and a set of search terms that a layperson would use to find cancer survivor stories online, we identified 3738 distinct sites. Of these, 106 met study criteria and contained 7995 total stories, including 1670 with an accompanying photo or video image of the survivor. Characteristics of both websites and survivor stories were coded. Results All racial minority groups combined accounted for 9.8% of online cancer survivor stories, despite making up at least 16.3% of prevalent cancer cases. Also notably underrepresented were stories from people of Hispanic ethnicity (4.1%), men (35.7%), survivors of colon cancer (3.5%), and older adults. Conclusions Because racial/ethnic minority cancer survivors are underrepresented in survivor stories available online, it is unlikely that this eHealth resource in its current form will help eliminate the disproportionate burden of cancer experienced by these groups.